DECONSTRUCTIVISM CHARACTERISTICS IN COLLECTIONS OF JAPANESE FASHION DESIGNERS AT THE END OF XX – EARLY XXI CENTURIES - Шевчук, Х. І. (Art and Design, 2021)
Purpose. The goal of this paper was to discover the main deconstruction in Japanese clothes designers creativity, methods of garment constructions, design and compositional features of fashion deconstruction. Methodology is based on system informative and visual analytical methods. Structural analysis of modification of compositional elements and method of comparative and historical analysis were used. Results. The paper describes basic principles and techniques of deconstruction in clothing design. The design and compositional features of deconstruction (shape, silhouette, construction, plastic, texture, decor, coloristic solution) in the works of Japanese clothing designers are determined. The basic principles of deconstruction in the works of Rey Kawakubo, Issey Miyake, Yohji Yamamoto are systematized and generalized, the combinations of features are inherent in each of the designers, their common and distinctive features are analyzed. Scientific novelty of the research is determined in definition and systematization of the main design and compositional features of deconstruction in clothing design. The basic principles of deconstruction in the collections of Japanese clothing designers are analyzed, the importance of the conceptual component of their work is emphasized. Practical significance. The systematic analysis of characteristics of clothes design deconstruction allows to use new interpretations and projecting unique clothes collections. The paper materials are supposed to be used in scientific research on deconstruction.